Engineered biosynthesis and characterization of disaccharide-pimaricin - Xiaoshan Zuo; Liqin Qiao; Yao Dong; Xing Jin; Zhongyuan Ren; Hao Cui (Microbial Cell Factories)
Abstract Background Disaccharide polyene macrolides exhibit superior water solubility and significantly reduced hemolytic toxicity compared to their monosaccharide counterparts, making them promising candidates for safer antifungal therapeutics. In this study, we engineered a Streptomyces gilvosporeus (pSET152-nppY) capable of producing disaccharide-pimaricin (DSP) through heterologous expression of the nppY gene, which encodes a glycosyltransferase responsible for the second sugar extension in the biosynthetic pathway. Results The novel compound was structurally characterized and designated disaccharide-pimaricin (DSP), featuring an aglycone identical to pimaricin and a unique disaccharide moiety (mycosaminyl-α1–4-N-acetylglucosamine). A purification protocol for DSP was established. Compared to pimaricin, DSP demonstrated a 50% reduction in antifungal activity, a 12.6-fold decrease in hemolytic toxicity, and a remarkable 107.6-fold increase in water solubility. Growth analysis revealed a delayed growth cycle in the mutant strain, suggesting that nppY expression may impose additional metabolic burden. Optimization of the fermentation medium using a statistical design identified an optimal formulation, with a maximum DSP titer of 138.168 mg/L. Conclusions This study underscores the potential of disaccharide polyene macrolides as safer antifungal agents and establishes a robust framework for engineering strains to produce these compounds. The findings provide critical insights into balancing biosynthetic efficiency and strain fitness, advancing the development of next-generation polyene antibiotics.